Lumibot at tumuklas using an explorer's toolkit to encourage interactivity in the National Museum of Anthropology for students ages 9-11 - Balanon, Gabrielle L.
The 21st century museum is expected to bridge the past with the present and be an engaging cultural agent that is accessible to all. In the Philippines, the National Museum of Anthropology takes the lead in preserving cultural and historical artifacts and presenting it to the public. However, an issue encountered by the researcher is the museum's lack of when it comes to engaging elementary age students who visit during school tours. The research part of this thesis explores how interactive museum exhibits engage young students according to their learning styles and which exhibits in the National Museum of Anthropology are appropriate for museum education. The researcher did ocular visits and structured observations in various museums; conducted interviews with National Museum, Archaeologists, and Educators; and referred to literature and works regarding museum and interactive exhibits. Analysis of the data gathering showed that interactive exhibits do not have to be high-tech to be interactive, and whilst they may not directly involve handling museum artifacts, they should help visitors explore real objects or real phenomena. Based on these results, the researcher created an explorer kit consisting of an activity book and a map of the museum that would encourage the students to interact with the exhibits and displays.